Carbon Dynamics in Rewetted Tropical Peat Swamp Forests - Darusman, T.; Murdiyarso, D.; Impron; Chaniago, I.A.; Lestari, D.P. (MDPI, 2022)
Degraded and drained peat swamp forests (PSFs) are major sources of carbon emissions in the forestry sector. Rewetting interventions aim to reduce carbon loss and to enhance the carbon stock. However, studies of rewetting interventions in tropical PSFs are still limited. This study examined the effect of rewetting interventions on carbon dynamics at a rewetted site and an undrained site. We measured aboveground carbon (AGC), belowground carbon (BGC), litterfall, heterotrophic components of soil respiration (Rh), methane emissions (CH4), and dissolved organic carbon (DOC) concentration at both sites. We found that the total carbon stock at the rewetted site was slightly lower than at the undrained site (1886.73 ± 87.69 and 2106.23 ± 214.33 Mg C ha−1, respectively). The soil organic carbon (SOC) was 1685 ± 61 Mg C ha−1 and 1912 ± 190 Mg C ha−1 at the rewetted and undrained sites, respectively, and the carbon from litterfall was 4.68 ± 0.30 and 3.92 ± 0.34 Mg C ha−1 year−1, respectively. The annual average Rh was 4.06 ± 0.02 Mg C ha−1 year−1 at the rewetted site and was 3.96 ± 0.16 Mg C ha−1 year−1 at the undrained site. In contrast, the annual average CH4 emissions were −0.0015 ± 0.00 Mg C ha−1 year−1 at the rewetted site and 0.056 ± 0.000 Mg C ha−1 year−1 at the undrained site. In the rewetted condition, carbon from litter may become stable over a longer period. Consequently, carbon loss and gain mainly depend on the magnitude of peat decomposition (Rh) and CH4 emissions.